2021
DOI: 10.3390/ncrna7010009
|View full text |Cite
|
Sign up to set email alerts
|

miR-24 Targets the Transmembrane Glycoprotein Neuropilin-1 in Human Brain Microvascular Endothelial Cells

Abstract: Neuropilin-1 is a transmembrane glycoprotein that has been implicated in several processes including angiogenesis and immunity. Recent evidence has also shown that it is implied in the cellular internalization of the severe acute respiratory syndrome coronavirus (SARS-CoV-2), which causes the coronavirus disease 2019 (COVID-19). We hypothesized that specific microRNAs can target Neuropilin-1. By combining bioinformatic and functional approaches, we identified miR-24 as a regulator of Neuropilin-1 transcription… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 94 publications
1
46
0
Order By: Relevance
“…It was hypothesized that the respiratory breakdown in COVID-19 patients may be at least in part caused by SARS-CoV-2 infecting respiratory centers in the medulla oblongata and the pons [ 90 , 91 ]. It was also proposed that neuropilin-1 (NRP1), a transmembrane receptor expressed in the respiratory and olfactory epithelium as well as in the CNS endothelial cells, may serve as an alternative cell receptor and facilitate SARS-CoV2 entry into the brain [ 36 , 37 , 102 ].…”
Section: Ace2 and Organ Tropism Of Sars-cov2mentioning
confidence: 99%
“…It was hypothesized that the respiratory breakdown in COVID-19 patients may be at least in part caused by SARS-CoV-2 infecting respiratory centers in the medulla oblongata and the pons [ 90 , 91 ]. It was also proposed that neuropilin-1 (NRP1), a transmembrane receptor expressed in the respiratory and olfactory epithelium as well as in the CNS endothelial cells, may serve as an alternative cell receptor and facilitate SARS-CoV2 entry into the brain [ 36 , 37 , 102 ].…”
Section: Ace2 and Organ Tropism Of Sars-cov2mentioning
confidence: 99%
“… 15 Additionally, other host factors enable and/or facilitate viral entry, such as transmembrane protease serine 2 (TMPRSS2), which acts on protein S priming; furin paired basic amino acid cleaving enzyme (FURIN), which activates protein substrates and pathogenic agents; and neuropilin-1 (NRP1), involved in angiogenesis and highly expressed on vascular cells and epithelia facing external environment, and which participates in tissue infiltration. 16 20 Although most research on virus entry focuses on ACE2, it is understandable that the availability of virus receptors and the interaction among cofactors help determine infectivity; in the case of SARS-CoV-2, cells with low ACE2 expression are also infected, which could be explained by the involvement of cofactors. 16 , 17 In addition, diverse genes have been reported to be upregulated in patients that develop severe COVID-19, possibly due to a direct correlation with the viral cycle in the human organism; these include ADAM metallopeptidase domain 10 (ADAM10), Toll-like receptor 3 (TLR3), histone acetyltransferase 1 (HAT1), histone deacetylase 2 (HDAC2), lysine demethylase 5B (KDM5B), sirtuin 1 (SIRT1), member renin-angiotensin system (RAS) oncogene family (RAB1A), and FURIN.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that miR-24 is expressed in human brain endothelial cells (ECs) and targets Neuropilin-1 [ 4 ], a co-factor needed for SARS-CoV-2 internalization that has been linked to cerebrovascular (CBV) manifestations of COVID-19 [ 5 ]. Henceforth, we hypothesized an association between plasma levels of endothelial EV miR-24 and the onset of CBV events in patients hospitalized for COVID-19.…”
mentioning
confidence: 99%
“…A SARS-CoV-2 test (RT-qPCR) was performed in all subjects to confirm or rule out the COVID-19 diagnosis. EC-EVs were extracted from the plasma collected from these patients via serial centrifugation and CD31 + magnetic isolation [ 1 ], and EC-EVs miR-24 levels were quantified as described [ 1 , 4 , 6 ].…”
mentioning
confidence: 99%